1984
DOI: 10.1037/0022-3514.46.1.145
|View full text |Cite
|
Sign up to set email alerts
|

On penetrating the "mask": The role of sagacity and acumen in a word-association/clinical-judgment task.

Abstract: The present study addressed aspects of Scheibe's (1979) description of the psychologist's modes of knowing another, specifically sagacity and acumen, as they applied to a videotaped clinical judgment task. The judgment task was patterned after classic research on the word-association lie-detection paradigm. Measures of empathy, understanding of defense mechanisms, and game strategy served as marker variables for the construct of acumen, whereas a task requiring alertness and attention served this purpose for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…The results also showed that strategy use interacted with knowledge of clues Subjects who did not use the strategy and who made many errors on the clue awareness task did quite poorly at the judgment task While this finding tends to imply that knowledge and vigilance are both sufficient for success (rather than both being necessary), the supplementary study showed that the most vigilant judges could be split into very competent and incompetent subgroups Moreover good judges were more hkely to have used valid clues plus a number of subtle idiosyncratic thief clues suggestive of guilty knowledge on the part of the thief Perhaps the most impressive evidence came from the difference between good and poor judges on a clue (pizza/parlor) that was highly diagnostic in both a qualitative and quantitative sense While poor judges consistently failed to recognize the significance of this clue, good judges seemed to use it more frequently over several tnals and then to take it for granted Hence the difference between good and poor judges (expressed as a phi coefficient) increased over five of the six appearances of this clue While good judges used clues suggestive of guilty knowledge, poor judges circled clues that were contradiagnostic of thieves Such a strategy would be appropriate for a "scientifically oriented" judge who wanted to proceed by first excluding "innocent" foils However, most people seem to use confirmatory strategies in testing hypotheses about others (Snyder & Campbell, 1980) So if we assume that good and poor judges sought to confirm their tentative hypotheses while circling clues, the poor judges' choice of contradiagnostic clues would account for their poor performance In effect they were taking "signs of innocence" to signify guilt This interpretation is consistent with other results m the study, specifically the finding that subjects high in knowledge (low m clue errors) attained higher hit rates There is one further explanation for the inaccuracy of the poor judges Recall that a majonty of poor judges circled the guilty/ innocent foil clue (see Table 4) while good judges did not The response "innocent" proved to be the modal reply to "guilty" for both thieves and foils (and observant judges should have recognized this) It IS possible, however, that poor judges attempted to read too much into suspects' answers, assuming that the guilty party would attempt to cover his or her innocence Conceivably, then, the poor judges outsmarted themselves by trying to be too sophisticated A similar finding occurred in a previous study where hit rate on the task correlated negatively with self-reported use of all clues in combination (Dollinger & Riger, 1984) An intriguing problem for future study is to distinguish between the judges who are merely slow to recognize implications and those who recognize significant information but overinterpret it by trying to be "too configural" in their thinking…”
Section: Tlie Concept Ofsagaettysupporting
confidence: 59%
See 3 more Smart Citations
“…The results also showed that strategy use interacted with knowledge of clues Subjects who did not use the strategy and who made many errors on the clue awareness task did quite poorly at the judgment task While this finding tends to imply that knowledge and vigilance are both sufficient for success (rather than both being necessary), the supplementary study showed that the most vigilant judges could be split into very competent and incompetent subgroups Moreover good judges were more hkely to have used valid clues plus a number of subtle idiosyncratic thief clues suggestive of guilty knowledge on the part of the thief Perhaps the most impressive evidence came from the difference between good and poor judges on a clue (pizza/parlor) that was highly diagnostic in both a qualitative and quantitative sense While poor judges consistently failed to recognize the significance of this clue, good judges seemed to use it more frequently over several tnals and then to take it for granted Hence the difference between good and poor judges (expressed as a phi coefficient) increased over five of the six appearances of this clue While good judges used clues suggestive of guilty knowledge, poor judges circled clues that were contradiagnostic of thieves Such a strategy would be appropriate for a "scientifically oriented" judge who wanted to proceed by first excluding "innocent" foils However, most people seem to use confirmatory strategies in testing hypotheses about others (Snyder & Campbell, 1980) So if we assume that good and poor judges sought to confirm their tentative hypotheses while circling clues, the poor judges' choice of contradiagnostic clues would account for their poor performance In effect they were taking "signs of innocence" to signify guilt This interpretation is consistent with other results m the study, specifically the finding that subjects high in knowledge (low m clue errors) attained higher hit rates There is one further explanation for the inaccuracy of the poor judges Recall that a majonty of poor judges circled the guilty/ innocent foil clue (see Table 4) while good judges did not The response "innocent" proved to be the modal reply to "guilty" for both thieves and foils (and observant judges should have recognized this) It IS possible, however, that poor judges attempted to read too much into suspects' answers, assuming that the guilty party would attempt to cover his or her innocence Conceivably, then, the poor judges outsmarted themselves by trying to be too sophisticated A similar finding occurred in a previous study where hit rate on the task correlated negatively with self-reported use of all clues in combination (Dollinger & Riger, 1984) An intriguing problem for future study is to distinguish between the judges who are merely slow to recognize implications and those who recognize significant information but overinterpret it by trying to be "too configural" in their thinking…”
Section: Tlie Concept Ofsagaettysupporting
confidence: 59%
“…
Based on Scheibe's (1979) concept of sagacity, the first purpose of this research was to assess the role of vigilance in a judgment task wherein subjects "read between the lines" of target persons' word associations Second, on the basis of the locus of control and cue explication literature, we tested the prediction that internals would be more successful judges than would externals only when a vigilant strategy was not emphasized in the task instructions In keeping with the first prediction, judges who used the vigilant strategy of circling what they thought to be clues did significantly better on the judgment task and on a postjudgment clue awareness task However, the results provided no support for the predicted interaction of instructions and locus of control These null findings emerged m a conceptual replication using a difFerent version of the judgment task and a different form of cue exphcation In both studies, externals did significantly better than did internals on the clue awareness task Finally, a supplementary study tested whether good-and poor-vigilant judges processed different clues in the judgment task Analyses of the clues circled while making judgments revealed that, relative to poor judges, good judges more often selected the most important clue in the task, and the discrepancy between good and poor judges increased over trials of the task Together with previous studies, the results provide strong support for conceptualizing the judgment task in terms of Scheibe's concept of sagacity Implicit in the enterprise of psychological research is the assumption that the causes of behavior often are not obvious Careful study and controlled investigation are necessary because the ways in which people think and act often have hidden influences Taking this logic one step further, we might assert that, if there is such a thing as Correspondence and requests for reprints should be addressed to S J Dollinger, Ddlingeretal "psychological-mmdedness," it would seem to involve the ability "to read between the lines of behavior "'One recent senes of studies has focussed on this ability to read between the lines in the context of a word-association clinicaljudgment task (Dollinger, Reader, Marnett, & Tylenda, 1983, Dollinger & Riger, 1984 In this task, subjects attempt to identify which of three "suspects" has imagined the commission of a theft In the videotape version of the task, they can make their judgments by recognizing the implications of suspects' word associations, facial expressions, and reaction times to vanous critical and noncntical stimulus words For the paper-and-pencil version of the task, judgments are based solely on word associations that are juxtaposed for the three suspects m each of the 10 judgment triads Across a senes of 6 studies, subject-judges have been quite successfiji at "catching the thief" Most samples yielded significantly-better-than-chance judgments as a group, and between 40% and 60% of individual subjects attained more hits than would be expected by chance Much of this work has been grounded in Scheibe's (1978Scheibe's ( , 1979) conceptualization of "the psychologist's prediction modes" (sagacitv, authority, and acumen), and the to-be-predicted person's tools for avoiding prediction (mirrors, masks, lies, and secrets) Scheibe's conceptual categories are particularly apropos in that, by the nature of the task, the suspects are protected by a kind of mask Moreover, they conceal a secret (the scnpt that they imagined performing), and the thief suspects may be motivated to lie about their guilt Finallv, the word association procedure involves reflection of an "image"the response word mirrors the stimulus word in a fi...
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Authority affords prediction via controlling the reinforcement contingencies in a situation; hence, it is less relevant to the task presently used. A series of studies suggest that the acumen mode is irrelevant to success at the task, but sagacity is quite relevant (Dollinger & Riger, 1984;Dollinger, in press). In particular, this research has shown that word associations but not affect expressions or reaction times provide the critical clue for judgment in this task, and successful judges more commonly report using just word associations.…”
mentioning
confidence: 99%